Anatolij Nikolaevich Sherstnev (on 80th birthday anniversary) - A.M. Bikchentaev; S.R. Nasyrov; E.A. Turilova (Учёные записки Казанского университета: Серия Физико-математические науки)
The paper describes the biography and the main scientific achievements of Professor Anatolij Nikolaevich Sherstnev.